Geochemical evidences on the origin and paleo‐oceanic depositional setting of the Naga Hills Ophiolite cherts, North East India. Issue 8 (1st May 2022) - Thong, Glenn T.; Imchen, Watitemsu; Walling, Temsulemba
Abstract : The Jurassic‐Cretaceous chert of the Naga Hills Ophiolite (NHO) is tectonically juxtaposed with the mafics (mostly basalts) and ultramafics along the Indo‐Myanmar Ranges (IMR), which constitute the southeastern extension of the Indus‐Yarlung‐Tsangpo Suture. Petrographic and geochemical studies were taken up to determine their origin and paleo‐oceanic depositional environments. Cryptocrystalline quartz is intimately mixed with iron oxides and clay minerals containing poorly preserved radiolarians. Geochemical signatures indicate a predominantly biogenic origin for the NHO cherts, which were derived from radiolarians and other siliceous microfossils. Rare earth elements and trace element abundances indicate predominant contribution by scavenging from seawater with the minor influence of low‐temperature hydrothermal activity. Most of the NHO cherts were deposited in an open ocean basin where oxic conditions prevailed. Geochemical signatures endorsed by field relations of chert, pillow basalts, and limestone within the oceanic plate indicate that chert formation continued in the vicinity of oceanic islands. Organic matter played a pivotal role in regulating oxic‐anoxic conditions during deposition, as evidenced by redox‐sensitive trace elements. These cherts, envisaged to have been originally part of the Tethys, were tectonically emplaced during the Middle Eocene. They now constitute part of the NHO along the IMR. Abstract : Geochemical data indicate the biogenic origin of Naga Hills Ophiolite chert, deposited in an open ocean basin distal from continental margins and hydrothermal activity. Evidence also indicates the formation of cherts over the seafloor plateaus or oceanic islands where the basin became relatively shallow and oxic.